Transforming Growth Factor Beta Receptor 3 Haplotypes in Sickle Cell Disease Are Associated with Lipid Profile and Clinical Manifestations - Rayra P. Santiago; Camylla V. B. Figueiredo; Luciana M. Fiuza; Sètondji C. M. A. Yahouédéhou; Rodrigo M. Oliveira; Milena M. Aleluia; Suellen P. Carvalho; Cleverson A. Fonseca; Valma M. L. Nascimento; Larissa C. Rocha; Caroline C. Guarda; Marilda S. Gonçalves (Hindawi Limited, 2020)
Individuals with sickle cell disease (SCD) present both chronic and acute inflammatory events. The TGF-β pathway is known to play a role in immune response, angiogenesis, inflammation, hematopoiesis, vascular inflammation, and cell proliferation. Polymorphisms in the transforming growth factor-beta receptor 3 (TGFBR3) gene have been linked to several inflammatory diseases. This study investigated associations between two TGFBR3 haplotypes and classical laboratory parameters, as well as clinical manifestations, in SCD. We found that individuals with the GG haplotype presented higher levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), triglycerides, non-HDL cholesterol, total proteins, and globulin than individuals with non-GG haplotypes. In addition, the GG haplotype was associated with a previous history of pneumonia. Individuals with the CGG haplotype presented increased plateletcrit, TC, LDL-C levels, and non-HDL cholesterol. The CCG haplotype was also associated with a previous history of pneumonia. Our findings suggest that individuals with the GG and CGG haplotypes of TGFBR3 present important alterations in lipid profile.